A user guide to the Innovation Lab for Small Scale Irrigation (ILSSI) baseline survey data: Ethiopia and Tanzania - Mekonnen, Dawit Kelemework; Bryan, Elizabeth; Choufani, Jowel; Davies, Emma; Ringler, Claudia; Passarelli, Simone (International Food Policy Research Institute, 2019)
The baseline survey data were collected in Ethiopia (November 2014 – December 2014), Tanzania (June 2015 – July 2015), and Ghana (November 2015 – February 2016) as part of the five-year Feed the Future Innovation Laboratory for Small-Scale Irrigation (ILSSI) project. The ILSSI project aims to benefit farmers of Ethiopia, Tanzania, and Ghana by improving effective use of scarce water supplies through interventions aimed at the scaling of small-scale irrigation for prosperity, nutrition and women’s empowerment. Due to differences in sampling methodology and survey timing, the Ghana survey data are not further described in the following. The ILSSI project is led by the Norman Borlaug Institute for International Agriculture at Texas A&M University, which also models the potential for upscaling of small-scale irrigation and environmental impacts and builds capacity using the Integrated Decision Support System (IDSS). The International Food Policy Research Institute (IFPRI) led the baseline and endline data collection as well as analysis of the gender, nutritional and health impacts of small-scale irrigation technologies, and the potential for upscaling of small-scale irrigation technologies to the national level in Ethiopia, Ghana and Tanzania. The International Water Management Institute (IWMI), the International Livestock Research Institute (ILRI), and North Carolina A&T State University field tested promising small-scale irrigation technologies in selected sites in each country and identified promising business models, small-scale irrigation technologies and opportunities to remove constraints to scaling. Local collaborators included in the data collection included the Association of Ethiopian Microfinance Institutions (Ethiopia), Sokoine University of Agriculture (Tanzania), and University of Development Studies (Ghana). The ILSSI baseline survey collected detailed household, individual, and plot-crop level data including the following modules: household roster; description of agricultural land (size, distance from home, soil type, registration, etc.); soil conservation; crop production, agricultural inputs, irrigation water sources, technologies and practices, and sales of agricultural products; labor (family, hired, and exchanged); livestock ownership, feed, and products; household income and expenditures; participation in social protection and development programs; shocks (agricultural and non-agricultural); dietary diversity and anthropometry; health; food security; and water supply, sanitation and hygiene (WASH).